2019
DOI: 10.2217/fon-2018-0708
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Exerts Cytotoxicity Dependent on Reactive Oxygen Species Accumulation in Non-Small-Cell Lung Cancer Cells

Abstract: Aim: Curcumin induces cytotoxic cell death in several human cancer cells. Here, we have investigated the effects of curcumin on non-small-cell lung cancer (NSCLC) with an aim to identify underlying mechanisms of its cytotoxic effect. Materials & methods: The effects of various concentrations of curcumin on the NSCLC cell lines A549 and SPC-A1 were evaluated by MTT assay, colony-forming assay and flow cytometry. Additionally, protein expression associated with different signaling pathways was assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…Radiation‐induced ROS leads to the accumulation of misfolded or abnormal proteins in the ER, which causes ER stress. Because ER stress is a critical inducer of apoptosis, previous studies focused on the link between ER stress and the enhanced radiosensitivity of cancer cells . Of note, Matsuo et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation‐induced ROS leads to the accumulation of misfolded or abnormal proteins in the ER, which causes ER stress. Because ER stress is a critical inducer of apoptosis, previous studies focused on the link between ER stress and the enhanced radiosensitivity of cancer cells . Of note, Matsuo et al .…”
Section: Discussionmentioning
confidence: 99%
“…Because ER stress is a critical inducer of apoptosis, previous studies focused on the link between ER stress and the enhanced radiosensitivity of cancer cells. [15][16][17][18] Of note, Matsuo et al found that overexpression of TMXs in 293 cells significantly attenuated ER stress and delayed the onset of ER stress-induced cell death. 13 These findings suggest that TMX1 and TMX2 might protect NSCLC against radiationinduced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A monocarbonyl analog of curcumin (Wz35) has the capability of stimulation of apoptotic cell death in NSCLC cells. During ER stress, unfolded protein response (UPR) is activated via the induction of eukaryotic initiation factor 2α (elF2α) phosphorylation (C. Wang et al, 2019, 2020). Then ATF4 undergoes upregulation that subsequently triggers CHOP and ER stress‐mediated apoptosis (E.‐S.…”
Section: Curcumin and Lung Cancermentioning
confidence: 99%
“…Another synthetic nanomaterial, chitosan nanoparticles loaded with demethoxycurcumin in combination with cisplatin, downregulates the expression levels of thymidine phosphorylase required for DNA self-repairing pyrimidine salvage pathways and induces apoptosis in non-small cell lung cancer (NSCLC) cell lines (38). Moreover, Wang et al (27) demonstrated that in NSCLC, curcumin decreases the mitochondrial transmembrane potential and increases the accumulation of reactive oxygen species (ROS) in cells, inducing DNA and mitochondrial damage-mediated apoptosis (39).…”
Section: Curcumin and Tumor Proliferation Previous Studies Havementioning
confidence: 99%